2012
DOI: 10.1093/toxsci/kfs022
|View full text |Cite
|
Sign up to set email alerts
|

The Anabolic Androgenic Steroid Fluoxymesterone Inhibits 11 -Hydroxysteroid Dehydrogenase 2-Dependent Glucocorticoid Inactivation

Abstract: Anabolic androgenic steroids (AAS) are testosterone derivatives used either clinically, in elite sports, or for body shaping with the goal to increase muscle size and strength. Clinically developed compounds and nonclinically tested designer steroids often marketed as food supplements are widely used. Despite the considerable evidence for various adverse effects of AAS use, the underlying molecular mechanisms are insufficiently understood. Here, we investigated whether some AAS, as a result of a lack of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…; Fürstenberger et al. ) 11βHSD1 leads to hypertension (Masuzaki et al. ) and to a metabolic syndrome (Masuzaki et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Fürstenberger et al. ) 11βHSD1 leads to hypertension (Masuzaki et al. ) and to a metabolic syndrome (Masuzaki et al.…”
Section: Discussionmentioning
confidence: 99%
“…11β-HSD2 activity measurement in intact SW-620 and MCF-7 cells was determined as described earlier [43]. Briefly, 100 000 SW-620 and 50 000 MCF-7 cells per well were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the androgen fluoxymesterone has shown to inhibit 11β-hydroxysteroid dehydrogenase, which may lead to decreased glucocorticoid inactivation and therefore to cortisol-induced mineralcorticoid receptor activation ending up in electrolyte disturbances. This could cause possible hypertension [ 67 ]. A recent study in recreational sports was conducted in 17 men given either the prohormone 3β-hydroxy-5α-androst-1-en-17-one or placebo where the treated group showed negative effects on cardiovascular and liver parameters [ 68 ].…”
Section: Adverse Effectsmentioning
confidence: 99%